UAV-SYSTEM FOR REMOTE ASSISTED MEDICAL DIAGNOSTICS AND PULMONOLOGICAL MONITORING OF POTENTIALLY INFECTED WITH COVID-19 PATIENTS "TREMBITA-CORONА UAV NAU" - Isaienko, Volodymyr; Kharchenko, Volodymyr; Astanin, Vyacheslav; Shchegel, Ganna; Olefir, Valentyna; Olefir, Oleksii; Olefir, Andrii; Khomych, Olha; Khomych, Volodymyr (Proceedings of National Aviation University (archive), 2020)
UAV-supported instrumental diagnostics system for remote acoustic investigation and monitoring of lungs for managing patients within the framework of telemedicine has been developed. The system includes a user set of control and measuring equipment and a UAV carrier for delivery and organization of the patient testing procedure.